Robust stabilization and weighted suppression of bounded disturbances in descriptor control systems - Kotov, T. O.; Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.925.51; 681.5.03 We establish necessary and sufficient conditions for the existence of dynamic regulators guaranteeing the prescribed estimation of the weighted damping level of bounded disturbances and the asymptotic stability of linear descriptor systems. An algorithm of construction of these regulators in the problems of robust stabilization and generalized $H_∞$-optimization is proposed for the descriptor systems with controlled and observed outputs. The main computational procedures of the algorithm are reduced to the solution of linear matrix inequalities with additional rank restrictions. The efficiency of the algorithm is demonstrated with the help of an illustrative example of descriptor stabilization system with bounded disturbances.